2017
DOI: 10.1007/s12144-017-9629-1
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Mental Training Questionnaire: Development and Validation

Abstract: Research in sports psychology has revealed that mental training is essential in the development of successful athletes. This project, comprised of five studies (a total of N = 2015) resulted in a novel approach towards the measurement of mental skills in sport. In Study 1 (N = 797) and Study 2 (N = 405) we used principal component analysis to identify and confirm the structure of a wide range of identified sport mental skills. Study 3 (N = 429) and Study 5 (N = 330) confirmed factorial structure of Polish and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…This seems to suggest that it is important to develop selfconfidence during the training and pre-competition phase as a component of an overall resilience building. For instance, coaches might plan the season schedule to help their athletes to build stronger self-confidence as a distinct component of mental training (Behnke et al, 2019). Consequently, athletes might be more resistant to misleading threatening information during competitions, i.e., inferiority feedback from the opposing team or fake news related to rivals' excellent shape.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that it is important to develop selfconfidence during the training and pre-competition phase as a component of an overall resilience building. For instance, coaches might plan the season schedule to help their athletes to build stronger self-confidence as a distinct component of mental training (Behnke et al, 2019). Consequently, athletes might be more resistant to misleading threatening information during competitions, i.e., inferiority feedback from the opposing team or fake news related to rivals' excellent shape.…”
Section: Discussionmentioning
confidence: 99%
“…Sports Mental Training was measured using a 10-item adapted version of the Sports Mental Training Questionnaire [ 31 ]. Four of the five factors were included: Foundational Skills (e.g., “I know my own value, my strengths, and weaknesses, and I plan how to improve them”; α = 0.67), Performance Skills (e.g., “When I am under pressure, I’m able to relax physically and mentally, so that I am ready to perform”; r = 0.47), Self-Talk (e.g., “I use self-talk to help myself overcome difficult times”; r = 0.56) and Mental Imagery (e.g., “During preparation for the jump I create real and accurate “inner films” planning possible obstacles and feeling sensations associated with the actual situation to come”; α = 0.70).…”
Section: Methodsmentioning
confidence: 99%
“…Mental training consists of a set of skills such as attention, focus and emotion regulation—and techniques ranging from self-talk to mental imagery. The use of mental training contributes to the building of a stronger mindset through the regulation of stress and emotions [ 31 ]. A series of research has indicated that athletes high in mental toughness exhibit more effective use of psychological strategies [ 17 ] and are characterized by an enhanced ability to prevent unwanted information from interfering with cognition [ 21 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, being a team player was measured using the interpersonal skills sub-scale of the Sport Mental Training Questionnaire (Behnke et al, 2019). The interpersonal skills subscale included four items scored on a 5-point Likert scale, ranging from 1 (Strongly disagree) to 5 (Strongly agree).…”
Section: Instrument Developmentmentioning
confidence: 99%